Brand Loyalty in The Context of Using Storytelling in New Media - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2020)
In today's highly competitive market conditions, participating in new media is an obligation for brands for the purpose of differentiation and popularity. In this regard, storytelling became an efficient method for content formation in new media marketing. The narration of contents allows brands to secure a visible place in consumers' minds. Therefore, contents became highly effective tools in establishing B2C (Business to Consumer) as well as B2B (Business to Business) connections. This study examines how the brands' application of digital storytelling effects brand loyalty. Within this context, digital storytelling's effect on self-brand connection is also elaborated. Furthermore, this research also investigates the participants' demographic qualities to analyze how they impact brand loyalty and self-brand connection in varying ways. As a result, this research concludes that digital storytelling plays an important role for consumers as it effectively forms brand loyalty and partially generates self-brand connection.
Keywords: Storytelling; Brand Loyalty; Self-Brand Connection; New Media; Narration; Advertising; CONNECTIONS